The Palgrave Handbook of Global Fantasy - Gomel, Elana; Gurevitch, Danielle (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"Hurray for this volume!! Breaking away from the familiar ground of Fantastical Anglophone texts read by English-language scholars, the essays here show the much needed glocality of contemporary scholarship. The first half of the essays probe the generic, methodological, and theoretical assumptions of fantasy, with each differing in approach but all coming together to build a dynamic yet operable paradigm. The second half, defined geographically, sweeps the globe to add voices, perspectives, and texts that have long gone largely unnoticed. The cumulative effect is a refreshing and exciting collection that truly magnifies the reach Fantasy Studies." -Keren Omry, University of Haifa This handbook is the first-of-its-kind comprehensive overview of fantasy outside the Anglo-American hegemony. While most academic studies of fantasy follow the well-trodden path of focusing on Tolkien, Rowling, and others, our collection spotlights rich and unique fantasy literatures in India, Australia, Italy, Greece, Poland, Russia, China, and many other areas of Europe, Asia, and the global South. The first part focuses on the theoretical aspects of fantasy, broadening and modifying existing definitions to accommodate the global reach of the genre. The second part contains essays illuminating specific cultures, countries, and religious or ethnic traditions. From Aboriginal myths to (self)-representation of Tibet, from the appropriation of the Polish Witcher by the American pop culture to modern Greek fantasy that does not rely on stories of Olympian deities, and from Israeli vampires to Talmudic sages, this collection is an indispensable reading for anyone interested in fantasy fiction and global literature. Elana Gomel is Associate Professor at the Department of English and American Studies at Tel-Aviv University. She is the author of five academic books and numerous articles on subjects such as narrative theory, posthumanism, science fiction, and Victorian culture. She is also an award-winning fiction writer. Danielle Gurevitch is cultural ethnologist and the director of the Multidisciplinary Studies at the Humanities at Bar-Ilan University. She is the author of several articles, editor of three academic books, and author of two. Speculative fiction, medieval literature, comparative literature, and gender studies are among her fields of expertise. Additionally, she is the chair of the faculty's "Dangoor Centre" for cultural diplomacy. .
1.Fantasy as Genre: On Defining the Field of Study -- 2. Allotopia: World-Building in Fantasy -- 3. Bio-Cultural Taxonomy -- 4. A Thousand and one Book: A Cross Cultural Approach to serialized fantasy -- 5.Children's Crosshatch Fantasy: Disturbing Portals, Crises and Comings-of-Age -- 6.Hybrid Secondary Worlds: Animal Fantasy -- 7."How did you go about saving a city? She googled it": Urban Fantasy Cities as Communities of citizens -- 8. Punk Subculture in Urban Fantasy: Life on the Border -- 9. History and Other (Colonial) Fantasies: Indigenous Time play in Cleverman -- 10. Chinese Danmei: Male-Male Romance, Women's Fantasy, and the Feminization of Labor in the Digital Age -- 11.Between Scylla & Charybdis: A Survey of Greece Fantasy Fiction -- 12.Re-imagining Hindu Mythology in the 21st Century: Amish Tripathi and Indian Fantasy Fiction in English -- 13. Looking for an Italian-Style Fantasy -- 14.Wilderness as Wonderland: Talmudic Stories and Modern Israeli Fantasy -- 15. Israeli Fantasy and Science Fiction: Fantastical Chronotopes and The Modern Promised Land -- 16.The Little Red Gloves: Apocalyptic Fantasy and the Bodhisattva of Mercy in a Japanese Picture Book on Hiroshima -- 17.Latin American Fantasy as Heterogeneous: Between Neomedievalism and LatinAmericanism -- 18.Cultural Appropriation of Poland's Fantasy: The Cold War Saga o Wiedźminie Moving into American Mainstream Culture -- 19.Syncretism in Russian fantasy -- 20.Mystification, Religious Imagery and Fantasy in Modern Tibetan Literature. .
Keywords: Fiction; Literature; Comparative literature; Popular Culture; Fiction Literature; World Literature; Comparative Literature; Popular Culture